A Traditional Remedy Revisited: Dichrostachys Cinerea in Urinary Stone Management - Bharti Bhatt; Sonam Rawat (AYUSHDHARA, 2025)
Urolithiasis, the formation of urinary calculi, is a prevalent condition associated with significant morbidity worldwide. Conventional therapies for urolithiasis, including pharmacological and surgical interventions, there is increasing interest in alternative therapies including herbal medicines. Herbs are used as medicine since time immemorial. Consequently, there is growing interest in exploring natural remedies for effective management. Dichrostachys cinerea, a versatile medicinal plant with a broad range of phytochemical constituents, holds potential in this domain due to its anti-inflammatory, antioxidant, and diuretic properties. Objective: To evaluate the effect of Dychrostachys cinerea in the management of urolithiasis (Mutrashmari). Material And Methods: Information was accessed by literature searches in different sources including ancient literature, journals, Science Direct, Pub Med and Google Scholar. The findings of this review paper highlight D. Cinerea as an important component of Indian traditional medicine. Conclusion: Our present findings suggest that anti-inflammatory, antioxidant, lithotripsic activity of D. cinerea is markedly effective in reduction of size and expulsion of calculus. This abstract explores the mechanistic insights and therapeutic potential of Dichrostachys cinerea in urolithiasis, emphasizing its pharmacological attributes and need for further preclinical and clinical studies. If validated, D. cinerea could offer a cost effective and natural alternative for preventing and managing urolithiasis, addressing the limitations of current therapeutic approaches.